Method for improving corrosion resistance of aluminide coating in sulfur-containing environment
By preparing and heat-treating the aluminide coating, the problem of insufficient corrosion resistance of the existing coating in sulfur-containing environment is solved, and the efficient corrosion resistance of the coating in flue gas environment is achieved.
Patent Information
- Application Number
- CN202510163382.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-06-03
AI Technical Summary
The existing aluminide coatings have insufficient corrosion resistance in sulfur-containing environments, resulting in rapid aging of the pipeline.
The coating slurry is prepared by weighing the solid-phase penetrant components and the liquid-phase components in proportion, and heat treatment is carried out under an inert atmosphere to form an aluminide corrosion-resistant coating.
It significantly improves the corrosion resistance of the aluminum coating in sulfur-containing flue gas environment. The seepage layer has a uniform structure and moderate thickness. Al atoms are fully diffused. The seepage layer and the substrate are well metallurgically combined, and are not easy to fall off.
Smart Images

Figure CN120079574A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material surface alloying and coating preparation, and particularly relates to a method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment. Background Art
[0002] In the presence of water or moisture, sulfides can cause pitting corrosion, uniform corrosion, stress corrosion cracking, etc. on the surface of pipe materials; in a sulfur-rich environment, the original corrosion rate of pipe materials increases significantly, especially under high temperature and high pressure conditions, the corrosion is more serious, which may lead to rapid aging of the pipeline. Therefore, it is of great practical significance to research and develop anti-oxidation and corrosion-resistant technologies for the inner and outer wall surfaces of pipes used in boiler units in a sulfur-containing environment.
[0003] To address the above problems, the most common and effective way is to use corrosion-resistant alloys or coatings to reduce the erosion of sulfides on pipe materials. The main methods for constructing coatings include: spraying method, dipping method, brushing method, electroplating method, and cladding method; for large-sized and complex-shaped pipes in the thermoelectric field, the preparation conditions of the brushing method are simple, but the coating formulation needs to be adjusted for different materials. The slurry needs to meet the following requirements: the viscosity and fluidity of the slurry, the coating method of the slurry, the curing and drying of the slurry, etc. These key points in the preparation process of the slurry method coating need to be correctly implemented, and the preparation process has high requirements. By strictly controlling the preparation process, the quality and durability of the coating can be effectively improved, thereby protecting the pipeline from the corrosion effects of factors such as sulfur-rich environments. In addition, traditional thermal diffusion aluminizing technology requires long-term heat preservation to enable aluminum atoms in the aluminizing agent to fully penetrate into the metal matrix, but this process has high energy consumption and low preparation efficiency. The thickness of the aluminide coating prepared is relatively thin, generally not exceeding 20μm, and this coating rapidly oxidizes and exfoliates in a sulfur-containing flue gas environment, thus losing the protective effect on the metal matrix. Summary of the Invention
[0004] The present invention aims to at least solve one of the technical problems of the short service life of existing thermal power pipelines and the limited life of aluminum coatings, and provides a method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment.
[0005] The present invention proposes a method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment, and the method includes:
[0006] Weigh the solid-phase aluminizing agent components and liquid-phase components in proportion, and prepare a coating slurry through stirring and ball milling; wherein, the solid-phase components include aluminizing source, modifier, filler, and accelerating agent, and the liquid-phase components include binder, curing agent, and catalyst;
[0007] Perform surface cleaning and preheating treatment on the workpiece to be plated in a sulfur-containing environment, and then spray the coating slurry onto the surface of the workpiece to be plated. After coating, perform drying and curing treatment;
[0008] The workpiece after coating and curing is placed under an inert atmosphere for high-temperature heat treatment, and an aluminide corrosion-resistant coating is obtained on the surface of the workpiece after cooling.
[0009] Optionally, in the solid-phase component, the infiltration source is Al powder, the modifier is Co and Pt powders, the filler is Al 2 O 3 , and the accelerating agent is La 2 O 3 .
[0010] Optionally, the solid-phase component includes:
[0011] 60-80% of Al powder;
[0012] 4-8% of Co powder;
[0013] 4-8% of Pt powder;
[0014] 5-30% of Al 2 O 3 ;
[0015] 0-5% of La 2 O 3 .
[0016] Optionally, in the liquid-phase component, the binder is water glass, the curing agent is MgO, and the catalyst is CrO 3 .
[0017] Optionally, the liquid-phase component includes:
[0018] 30-70% of water glass;
[0019] 20-40% of MgO solution;
[0020] 10-30% of CrO 3 solution.
[0021] Optionally, the solid-liquid ratio of the solid-phase component and the liquid-phase component is 10:(3-7) g / mL.
[0022] Optionally, the temperature of the preheat treatment is 240 °C, and the time is 30-60 min.
[0023] Optionally, the spraying pressure of the coating slurry is 0.5-2 MPa, the coating thickness is 0.1-5 mm, and the coating coverage rate is not less than 98%.
[0024] Optionally, the temperature of the curing treatment is 300-450 °C, and the time is 24-48 h.
[0025] Optionally, the temperature of the high-temperature heat treatment is 1000 - 1150 °C, the time is 10 - 15 min, and the heat treatment atmosphere is an inert gas Ar or N 2 。
[0026] The present invention provides a method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment. The method includes: weighing solid-phase penetrant components and liquid-phase components in proportion, and preparing a coating slurry for use after stirring and ball milling; wherein, the solid-phase components include a penetration source, a modifier, a filler, and an accelerating agent for penetration, and the liquid-phase components include a binder, a curing agent, and a catalyst; performing surface cleaning and preheating treatment on the workpiece to be plated in a sulfur-containing environment, then spraying the coating slurry onto the surface of the workpiece to be plated, and performing drying and curing treatment after coating; placing the coated and cured workpiece in an inert atmosphere for high-temperature heat treatment, and obtaining an aluminide corrosion-resistant coating on the surface of the workpiece after cooling, and performing treatment on the coating residue. The preparation method is simple, and there is no need to adjust the formula for different materials, meeting the requirements of various workpiece materials. In a sulfur-containing flue gas environment, the modified elements can form stable sulfides and eutectic structures, improving the corrosion resistance of the aluminide coating in the flue gas environment. The prepared infiltration layer has a uniform microstructure, a moderate thickness, sufficient Al atom diffusion, a good metallurgical bond between the infiltration layer and the substrate, and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flowchart of a method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment according to an embodiment of the present invention;
[0028] Figure 2 is a microscopic morphology diagram of the infiltration layer structure in Embodiment 1 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0029] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the disclosure. The described embodiments are a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the described embodiments of the present invention without creative efforts fall within the protection scope of the present invention.
[0030] As Figure 1 shown, the present invention provides a method S100 for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment, including the following specific steps S110 - S130:
[0031] S110. Weigh solid-phase penetrant components and liquid-phase components in proportion, and prepare a coating slurry for use after stirring and ball milling.
[0032] In step S110, the solid-phase components include a permeation source, a modifier, a filler, and an infiltration accelerator. Among them, the permeation source is Al powder, the modifier is Co and Pt powders, the filler is Al 2 O 3 , and the infiltration accelerator is La 2 O 3 , where the Al, Co, and Pt powders are all sieved through a 1000-mesh sieve.
[0033] In some preferred embodiments, the preparation method of the solid-phase components of the slurry is as follows: Weigh the solid-phase components by mass percentage, including 60-80% Al, 4-8% Co, 4-8% Pt, 5-30% Al 2 O 3 and 0-5% La 2 O 3 . The total mass of the solid-phase components remains 100%. After weighing, they are ball-milled and mixed by a planetary ball mill at a ball-milling speed of 350-400 rpm for 6-24 h.
[0034] In the present invention, by introducing modifier elements such as Co and Pt elements with strong binding force to Al, the uphill diffusion of Al atoms is promoted, thereby increasing the infiltration rate. The thickness of the prepared coating can reach 22-43 μm. Secondly, by co-modifying the aluminide anti-oxidation coating with Co and Pt, it helps to improve the thermal corrosion resistance of the coating in a sulfur-containing flue gas corrosion environment. Among them, in a sulfur-containing flue gas environment, the Co modifier element can form stable sulfides and eutectic structures, improving the corrosion resistance of the aluminide coating in the flue gas environment. The Pt element modification can provide a channel for the Al element to form a dense oxide film, enhancing the bonding force between the oxide film and the substrate and effectively inhibiting internal oxidation and internal sulfidation.
[0035] In step S110, the liquid-phase components include a binder, a curing agent, and a catalyst. Among them, the binder is water glass, the curing agent is MgO, and the catalyst is CrO 3 .
[0036] In some preferred embodiments, the preparation method of the liquid-phase components of the slurry is as follows: The liquid-phase components contain 30-70% water glass, 20-40% MgO solution, and 10-30% CrO 3 solution. After weighing the water glass, the curing agent, and the catalyst in proportion, they are fully mixed, stirred, reacted, and filtered for 4-8 h to obtain the liquid-phase components.
[0037] In the present invention, by adding La 2 O 3 and CrO 3 to the coating slurry components, the effects of accelerating infiltration and activation are achieved, improving the infiltration rate and the coating quality.
[0038] Further, the solid-liquid ratio of the solid component to the liquid component is 10:(3-7) g / mL, for example, 10:3, 10:4, 10:5, 10:6, 10:7, etc.
[0039] Furthermore, the method for preparing the coating slurry is as follows: Mix the two components at a solid-liquid ratio of 10 g: 3-7 mL, stir well for 2-4 h, and then place them in a planetary ball mill for ball milling and mixing. The ball milling speed is 350-400 rpm and the time is 6-24 h, and finally a uniformly mixed coating slurry is obtained.
[0040] S120. Clean and preheat the workpiece to be plated in a sulfur-containing environment, and then spray the coating slurry onto the surface of the workpiece to be plated. After coating, perform drying and curing treatments.
[0041] Specifically, take out the workpiece to be plated, use a high-pressure water gun to clean the surface for 5-10 min to remove oil stains, dust, etc. on the surface of the workpiece and remove the oxide scale, and rinse it clean with alcohol or acetone to provide a clean and metallic luster surface for the subsequent coating slurry. Preheat the workpiece at 240 °C by medium frequency for 30-60 min, and coat the slurry at one time to an appropriate thickness at a spraying pressure of 0.5-2 MPa. Do not coat in multiple layers. Keep the coating layer thickness at 0.1-5 mm and the coating coverage rate not less than 98%. If the slurry layer is too thin, it is not sufficient to provide an adequate infiltration source, and if it is too thick, it is prone to cracking and peeling, affecting the uniformity of the infiltration layer thickness; after coating, air-dry the workpiece naturally for 24-48 h.
[0042] In this embodiment, the segmented slurry curing process combining natural air drying and medium and low temperature curing effectively avoids the problems of microcracks and micropores generated by the thermal stress in the slurry layer during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.
[0043] S130. Place the coated and cured workpiece under an inert atmosphere for high-temperature heat treatment, and after cooling, an aluminide corrosion-resistant coating is obtained on the surface of the workpiece, and the coating residue is treated.
[0044] Specifically, to prevent the rapid evaporation of the slurry components at high temperatures, the workpiece is heat-treated by rapid heating and short-time heat preservation, and then air-cooled to room temperature; the heat treatment temperature is 1000-1150 °C, the heat preservation time is 10-15 min, and the inert gas is Ar or N 2 ; After the heat treatment, rinse the residue on the surface of the workpiece with a high-pressure water gun or high-pressure air flow, and air-dry it naturally. By performing heat treatment under an inert atmosphere, the present invention effectively avoids phenomena such as oxidation and hydrogen embrittlement that may occur in austenitic steel, protects the workpiece substrate while improving the infiltration rate.
[0045] In this embodiment, by adjusting the main process parameters such as the content of the solid-phase penetrant components, the content of the modifying elements, the solid-liquid ratio of the slurry, the spraying pressure of the slurry, and the heat treatment parameters, an aluminide corrosion-resistant coating with a thickness of 22 - 43 μm and an Al atomic content of 23% - 38% and showing good metallurgical bonding can be prepared. Moreover, this corrosion-resistant coating is mainly composed of elements such as Al, Ni, Cr, and Fe. Among them, Al, as the main corrosion-resistant element, combines with the Ni and Fe elements in the substrate to form intermetallic compounds in the coating, and can generate a uniform and dense Al 2 O 3 oxide film during service, thereby protecting the base metal from being corroded by sulfur-containing media. Within a certain range, the higher the Al element content in the coating, the better the corrosion resistance of the coating. However, when the Al content in the coating is too high, Fe 2 Al 5 phases will be formed, resulting in an increase in the brittleness of the coating. When the Al content in the coating is 23% - 38%, it is more appropriate. Further, the obtained aluminide coating has an antioxidant ability 17 - 61 times higher than that of the base material in a 600 °C pure water vapor environment and 21 - 74 times higher than that of the base material in a 650 °C pure water vapor environment. In addition, the heat corrosion resistance of the Co and Pt co-modified aluminide coating in a flue gas environment is 12 - 24 times higher than that of the unmodified aluminide coating, which shows that the aluminide corrosion-resistant coating prepared by the method of the present invention effectively improves the antioxidant and corrosion resistance of the alloy base material in the service environment.
[0046] Furthermore, the penetration layer structure prepared by the present invention is uniform, with a moderate thickness, and sufficient Al atom diffusion. The penetration layer shows good metallurgical bonding with the substrate and is not easy to fall off. It is applicable to austenitic steels and superalloy components used in large boilers, oil and gas field transportation pipelines, etc., with large length-diameter ratios and various complex-shaped workpieces, that is, applicable to various complex-shaped metal workpieces. There is no need to adjust the slurry formula for different material workpieces, and it has extremely strong universality and excellent industrial batch production benefits.
[0047] Next, several specific examples will be combined to further illustrate the method for improving the corrosion resistance of aluminide coatings in a sulfur-containing environment:
[0048] Example 1
[0049] Step 1: Weigh the solid-phase components according to the mass ratio, including 60% Al, 5% Co, 5% Pt, 25% Al 2 O 3 and 5% La 2 O 3 , place them in a planetary ball mill and ball mill at 400 rpm for 24 h to obtain a solid-phase penetrant; subsequently, proportionally prepare water glass, a 30% MgO solution, and a 20% CrO 3The solution is subjected to sufficient mixing, stirring, reaction, and filtration for 8 h to obtain a liquid-phase component; finally, the solid-phase component and the liquid-phase component are mixed at a solid-liquid ratio of 10 g: 3 mL, stirred thoroughly for 4 h, and then placed in a planetary ball mill for ball milling at 400 rpm for 24 h. After completion, a uniformly mixed slurry, i.e., the coating slurry, is obtained.
[0050] Step 2: Clean the surface of the workpiece with a high-pressure water gun for 5 min and rinse it thoroughly with alcohol or acetone; subsequently, preheat the workpiece at 240 °C by medium-frequency for 45 min, and apply the slurry to a thickness of 3 mm at a spraying pressure of 2 MPa at one time, ensuring that the coating coverage rate is not less than 98%; then, air-dry the workpiece naturally for 48 h and cure it at 450 °C for 48 h.
[0051] Step 3: Place the coated metal pipe under Ar for heat treatment at a heat treatment temperature of 1000 °C and a holding time of 15 min. After completion, rinse the residue on the surface of the workpiece with a high-pressure water gun or high-pressure air flow and air-dry it naturally.
[0052] As shown in Table 1, the thickness of the infiltration layer obtained in this example is 27.2 μm, and the Al atomic content is 25.3%. The cross-sectional morphology of the infiltration layer is as Figure 2 shown. It is found that the microstructure of the infiltration layer is uniform, the thickness is appropriate, the Al atoms are diffused sufficiently, and the infiltration layer and the matrix show good metallurgical bonding and are not easy to fall off.
[0053] Example 2
[0054] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, and the thickness of the infiltration layer obtained therefrom is 36.5 μm, and the Al atomic content is 29.7%.
[0055] Example 3
[0056] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:7, and the thickness of the infiltration layer obtained therefrom is 31.2 μm, and the Al atomic content is 27.4%.
[0057] Example 4
[0058] The preparation process of the method in this example is the same as that in Example 2. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, and the spraying pressure is 0.5 MPa. The thickness of the infiltration layer obtained therefrom is 27.6 μm, and the Al atomic content is 27.2%.
[0059] Example 5
[0060] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, and the thickness of the infiltration layer obtained thereby is 39.4 μm, and the Al atom content is 33.2%.
[0061] Example 6
[0062] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, the medium-temperature curing time is 24 h, and the thickness of the infiltration layer obtained thereby is 34.5 μm, and the Al atom content is 30.4%.
[0063] Example 7
[0064] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, the medium-temperature curing temperature is 300 °C, the time is 24 h, and the thickness of the infiltration layer obtained thereby is 32.3 μm, and the Al atom content is 27.3%.
[0065] Example 8
[0066] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, the temperature of the high-temperature heat treatment is 1100 °C, and the thickness of the infiltration layer obtained thereby is 38.7 μm, and the Al atom content is 34.5%.
[0067] Example 9
[0068] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, the temperature of the high-temperature heat treatment is 1100 °C, the time is 10 min, and the thickness of the infiltration layer obtained thereby is 36.8 μm, and the Al atom content is 33.5%.
[0069] Example 10
[0070] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid-phase component to the liquid-phase component is 10:5, the spraying pressure is 2 MPa, the time of the high-temperature heat treatment is 10 min, and the thickness of the infiltration layer obtained thereby is 36.4 μm, and the Al atom content is 33.6%.
[0071] Example 11
[0072] The preparation process of the method in this example is the same as that in Example 1. As shown in Table 1, the difference is that the solid-liquid ratio of the solid phase component to the liquid phase component is 10:5, the spraying pressure is 2 MPa, the temperature of the high-temperature heat treatment is 1150 °C, and the time is 10 min. The obtained infiltration layer thickness is 41.4 μm, and the Al atom content is 35.8%.
[0073] In summary, through the analysis and research of the above examples, the measured infiltration layer thickness is about 22 - 43 μm, and the Al atom content is 23% - 38%. The specific results are shown in Table 1.
[0074] In summary, the corrosion resistance of the aluminide coatings prepared in Examples 1 - 11 was tested in coal ash / flue gas at 750 °C. The mass changes (mg / cm 2 ) of the coatings after corrosion for 50, 200, 300, and 500 h in the coal ash / flue gas environment at 750 °C are shown in Table 2.
[0075] Table 1 Process parameters and infiltration layer parameters of Examples 1 - 11
[0076]
[0077]
[0078] Table 2 Mass changes (mg / cm 2 ) of the coatings prepared in Examples 1 - 11 in coal ash / flue gas at 750 °C
[0079]
[0080] Example 12
[0081] Step 1: Weigh the solid-phase components by mass ratio, including 80% Al, 5% Co, 5% Pt, 5% Al 2 O 3 and 5% La 2 O 3 , to obtain the solid-phase infiltrant. Subsequently, mix water glass and a 20% CrO 3 solution in proportion. After 8 h of sufficient mixing, stirring, reaction, and filtration, the liquid-phase component is obtained. Finally, mix the solid-phase and liquid-phase components at a solid-liquid ratio of 10 g:5 ml, stir well for 4 h, and then place them in a planetary ball mill for ball milling at 400 rpm for 24 h. After completion, a uniformly mixed slurry, i.e., the coating slurry, is obtained.
[0082] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 240°C for 45 minutes, and apply the slurry to a thickness of 3mm at a time with a spraying pressure of 2MPa, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.
[0083] Step 3: Place the coated metal pipe under Ar for heat treatment at a temperature of 1050°C and a holding time of 15 minutes. After completion, use a high-pressure water gun or high-pressure airflow to flush the residue on the workpiece surface and let it dry naturally.
[0084] Embodiment 13
[0085] Step 1: Weigh the solid phase components according to the mass ratio, including 70% Al, 5% Co, 5% Pt, and 15% Al 2 O 3 and 5% La 2 O 3 , and placed it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase infiltration agent; then, water glass and 20% CrO were mixed according to the proportion. 3 The solution was fully mixed, stirred, reacted and filtered for 8 hours to obtain a liquid component; finally, the solid and liquid components were mixed at a solid-liquid ratio of 10g:5ml, and after fully stirring for 4 hours, they were placed in a planetary ball mill at 400rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.
[0086] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 240°C for 45 minutes, and apply the slurry to a thickness of 3mm at a time with a spraying pressure of 2MPa, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.
[0087] Step 3: Place the coated metal pipe under Ar for heat treatment at a temperature of 1050°C and a holding time of 15 minutes. After completion, use a high-pressure water gun or high-pressure airflow to flush the residue on the workpiece surface and let it dry naturally.
[0088] Embodiment 14
[0089] Step 1: Weigh the solid phase components according to the mass ratio, including 65% Al, 6% Co, 6% Pt, and 18% Al 2 O 3 and 5% La 2 O 3, it is placed in a planetary ball mill and ball milled at 400 rpm for 24 h to obtain a solid-phase infiltrant; subsequently, water glass and 20% CrO 3 solution are proportionally prepared, and after 8 h of sufficient mixing, stirring, reaction, and filtration, a liquid-phase component is obtained; finally, the solid-phase and liquid-phase components are mixed at a solid-liquid ratio of 10 g:5 ml, stirred thoroughly for 4 h, then placed in a planetary ball mill and ball milled at 400 rpm for 24 h. After completion, a uniformly mixed slurry, i.e., the coating slurry, is obtained.
[0090] Step 2: Clean the surface of the workpiece with a high-pressure water gun for 5 min, and rinse it thoroughly with alcohol or acetone; subsequently, preheat the workpiece at 240 °C by medium-frequency for 45 min, and spray the slurry onto a thickness of 3 mm at a spraying pressure of 2 MPa at one time, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 48 h and cure it at 450 °C for 48 h.
[0091] Step 3: Place the coated metal pipe under Ar for heat treatment, with a heat treatment temperature of 1050 °C and a holding time of 15 min. After completion, rinse the residue on the surface of the workpiece with a high-pressure water gun or high-pressure air flow, and air-dry it naturally.
[0092] Example 15
[0093] Step 1: Weigh the solid-phase components according to the mass ratio, including 70% Al, 4% Co, 8% Pt, 13% Al 2 O 3 and 5% La 2 O 3 , place it in a planetary ball mill and ball mill at 400 rpm for 24 h to obtain a solid-phase infiltrant; subsequently, proportionally prepare water glass and 20% CrO 3 solution, and after 8 h of sufficient mixing, stirring, reaction, and filtration, a liquid-phase component is obtained; finally, the solid-phase and liquid-phase components are mixed at a solid-liquid ratio of 10 g:5 ml, stirred thoroughly for 4 h, then placed in a planetary ball mill and ball milled at 400 rpm for 24 h. After completion, a uniformly mixed slurry, i.e., the coating slurry, is obtained.
[0094] Step 2: Clean the surface of the workpiece with a high-pressure water gun for 5 min, and rinse it thoroughly with alcohol or acetone; subsequently, preheat the workpiece at 240 °C by medium-frequency for 45 min, and spray the slurry onto a thickness of 3 mm at a spraying pressure of 2 MPa at one time, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 48 h and cure it at 450 °C for 48 h.
[0095] Step 3: Place the coated metal pipe under Ar for heat treatment, with a heat treatment temperature of 1150 °C and a holding time of 10 min. After completion, rinse the residue on the surface of the workpiece with a high-pressure water gun or high-pressure air flow, and air-dry it naturally.
[0096] Example 16
[0097] Step 1: Weigh the solid phase components according to the mass ratio, including 70% Al, 8% Co, 4% Pt, and 13% Al 2 O 3 and 5% La 2 O 3 , and placed it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase infiltration agent; then, water glass and 20% CrO were mixed according to the proportion. 3 The solution was fully mixed, stirred, reacted and filtered for 8 hours to obtain a liquid component; finally, the solid and liquid components were mixed at a solid-liquid ratio of 10g:5ml, and after fully stirring for 4 hours, they were placed in a planetary ball mill at 400rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.
[0098] Step 2: Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes, and rinse it with alcohol or acetone; then, preheat the workpiece at 240°C for 45 minutes, and apply the slurry to a thickness of 3mm at a time with a spraying pressure of 2MPa, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours, and cure it at 450°C for 48 hours.
[0099] Step 3: Place the coated metal pipe under Ar for heat treatment at a temperature of 1150°C and a holding time of 15 minutes. After completion, use a high-pressure water gun or high-pressure airflow to flush the residue on the workpiece surface and let it dry naturally.
[0100] The present invention proposes a method for improving the corrosion resistance of an aluminide coating in a sulfur-containing environment, which has the following beneficial effects compared to the prior art:
[0101] First, the present invention adds La to the coating slurry components. 2 O 3 and CrO 3 , which has the effect of promoting penetration and activation, and improves the penetration rate and coating quality;
[0102] Second, the present invention introduces Co and Pt elements to co-modify the aluminide anti-oxidation coating, thereby improving the thermal corrosion resistance of the coating in a sulfur-containing flue gas corrosive environment;
[0103] Third, the present invention effectively avoids the oxidation and hydrogen embrittlement that may occur in austenitic steel by heat treatment under an inert atmosphere, thereby protecting the workpiece matrix and increasing the penetration rate;
[0104] Fourth, the present invention prepares the coating through a slurry coating process, which is suitable for metal workpieces of various complex shapes and has strong universality;
[0105] Fifth, the present invention prepares the coating through an integrated production line, which has high coating production efficiency, controllable thickness, high process repeatability, and extremely strong practicability.
[0106] It can be understood that the above embodiments are merely exemplary embodiments adopted to illustrate the principle of the present invention. However, the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also regarded as the protection scope of the present invention.
Claims
1. A method for improving the corrosion resistance of an aluminide coating in a sulfur-containing environment, characterized in that: The method comprises: The solid phase infiltration agent component and the liquid phase component are weighed in proportion, and a coating slurry is prepared after stirring and ball milling; wherein the solid phase component includes an infiltration source, a modifier, a filler, and an infiltration catalyst, and the liquid phase component includes a binder, a curing agent, and a catalyst; The surface of the workpiece to be plated in the sulfur-containing environment is cleaned and preheated, and then the coating slurry is sprayed onto the surface of the workpiece to be plated, and after the coating is completed, it is dried and cured; The coated and cured workpiece is placed in an inert atmosphere for high-temperature heat treatment, and an aluminide corrosion-resistant coating is obtained on the surface of the workpiece after cooling.
2. The method according to claim 1, characterized in that In the solid phase components, the infiltration source is Al powder, the modifier is Co and Pt powder, the filler is Al2O3, and the infiltration catalyst is La2O3.
3. The method according to claim 2, characterized in that The solid phase components include: 60-80% Al powder; 4-8% Co powder; 4-8% Pt powder; 5-30% Al2O3; 0-5% La2O3.
4. The method according to claim 1, characterized in that: In the liquid phase component, the binder is water glass, the curing agent is MgO, and the catalyst is CrO3.
5. The method according to claim 4, characterized in that The liquid phase components include: 30-70% water glass; 20-40% MgO solution; 10-30% CrO3 solution.
6. The method according to any one of claims 1 to 5, characterized in that: The solid-liquid ratio of the solid phase component to the liquid phase component is 10:(3-7) g / mL.
7. The method according to any one of claims 1 to 5, characterized in that: The preheating treatment is performed at a temperature of 240° C. for a period of 30-60 minutes.
8. The method according to any one of claims 1 to 5, characterized in that: The coating slurry spraying pressure is 0.5-2MPa, the coating layer thickness is 0.1-5mm, and the coating coverage is not less than 98%.
9. The method according to any one of claims 1 to 5, characterized in that: The curing treatment is carried out at a temperature of 300-450° C. and for a time of 24-48 hours.
10. The method according to any one of claims 1 to 5, characterized in that: The temperature of the high temperature heat treatment is 1000-1150°C, the time is 10-15 minutes, and the heat treatment atmosphere is an inert gas Ar or N2.